A generalization of contraction principle. (1981) - Ghosh, K. M.
Abstract : In this paper, a generalized mean value contraction is introduced. This contraction is an extension of the contractions of earlier researchers and of the generalized mean value non-expansive mapping. Using the generalized mean value contraction, some fixed point theorems are discussed.